Antecedents of Chinese adolescents' purchase intention for local brands: the moderating influence of materialistic values. Issue 4 (13th June 2016) - Shi, Bing; Zhang, Dan; Xie, Hongling; Zhou, Yinghui
Abstract : Purpose: This study aims to examine factors affecting Chinese adolescents' purchase intention for local brands; this study focuses on the effects of perceived social status value and materialistic values. Design/methodology/approach: A theoretical model relating perceived social status value of brands to purchase intention, including materialistic values as a moderator, was developed and tested, using a sample of 587 Chinese adolescent respondents. Another experimental study examined the variability of the moderation of materialistic values across different levels of peer pressure in a product usage occasion. Findings: Perceived social status value associated with local and foreign brands significantly influences purchase intention for local brands. Moreover, influence of perceived social status value of local versus foreign brands on local brand purchase intention is greater for materialistic adolescents. Additionally, the moderation of materialistic values is found in a product usage occasion with high peer pressure, but not in an occasion with low peer pressure. Research limitations/implications: The findings show that perceived social status value associated with brands shapes purchase intention for local brands. The moderating effect of materialistic values is complex and suggests further research. The study's scope is limited to Chinese adolescents. Practical implications: The findings provide understanding of the drivers of purchase intention, and thus serve as a guideline for Chinese firms and foreign marketers seeking to enter the growing Chinese market, as well as consumer educators in China. Originality/value: This study contributes to the limited empirical research into the factors shaping country-of-origin effects. Moreover, the findings suggest the need to consider the moderating role of materialistic values on purchase intention for local brands.